Od abstraktnosti mita o Faroniki do alegorične konkretizacije teorije o GajiFrom the Abstract Myth about Faronika to the Allegoric Concretisation of the Theory of Gaia - Pangeršič, Irena (Studia mythologica Slavica, 2012)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In the article is discussed the connection between the myth about the fish Faronika and the metheorological and seismological phenomenons on the planet Earth.